Habermas’ Concept of “Lebenswelt” and System and Its Implication for the Position of Religion in Public Life - Sunaryo Sunaryo (Jurnal Filsafat "WISDOM", 2023)
The concept of “Lebenswelt” (the lifeworld) and the system are essential in Jürgen Habermas's thought. Habermas understands Lebenswelt as background knowledge that people take for granted naively. It becomes the horizon of their daily communication. He emphasizes the importance of coupling Lebenswelt and system. The uncoupling will make society get loss of meaning. Then we ask how he understands the position of religion in public life. How should we place religion as a part of Lebenswelt in making public law? To answer the question, we did the library research by exploring Habermas's works and his commentators. Then I conclude that Habermas offers accommodative participation to religion in public life through discourse. In the discourse, views inspired by religion can be put forward in the public sphere as far as they undergo a rationalization process. They should be openly discussed and tested instead of being taken for granted naively. Views inspired by religion will be accepted as long as they are rational. Discourse practice requires religious groups to be more mature and rational in formulating their ideas in the public sphere. Religious ideas are no longer positioned as closed and anti-criticism.